Computational Analysis Of The Effect V241F KCNQ1 Mutation On Cardiac Ventricular Mechanical Responses: Simulation Method. - Fakhmi Adi Rasyidin; Lee Hyunsoo; Ki Moo Lim (eProceedings of Engineering, 2018)
Abstract Several studies have found genetic mutations, which affect characteristics of specific ion channels and cause cardiac arrhythmia such as atrial and ventricular fibrillation [1]. Study about understanding the genetic predisposition, modeling cardiac tissue to apply on simulation study, and how genetic mutation influence the Atrial and Ventricular Fibrillation challenge the researcher to solve it. To construct a computational model of a cardiovascular system, we used 3D finite element model of a failing human ventricle, combined with a lumped model of the circulatory system [12]. In a 3D cardiac tissue CAD electromechanical model, we analyze the propagation wave in 2 conditions, normal sinus rhythm and reentry. During normal sinus pacing, the electrical stimulation applied from Purkinje fibers tissue. In our research, we investigate the effect of V241F mutation in canine ventricular in failure state using the computational method. This is the first study to implement a finite element of an image based on the electromechanical model for the heart, to investigate cardiac electrophysiology and mechanics for V241F mutation. The mutation V241F effected the mechanical behavior according to electrical as an input. In a single cell, V241F with pure mutation shortened the ventricular APD around 67% and 33% for intermediate variant mutation. Keywords: Finite Element Model (FEM), Mechanical simulation, Cardiovascular